Mental Health, AI-based Care Robots and Fair Access to Healthcare - Kropf, Mario (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Health is usually seen as an important prerequisite for the realization of life goals and therefore has a great meaning in society. Many authors and their perspectives also make it clear that health can be seen as a moral value that is ethically relevant and must be promoted. In recent years, numerous crises, armed conflicts, digitalization and, more generally, the fast pace of life in society, have contributed to raise awareness of mental health. This article deals with an ethical analysis of mental health in the context of AI-based care robots. Robot companions in the care sector are increasingly being used, and this trend will continue in the near future. However, the question arises as to what extent these machines can contribute to mental health when interacting with people receiving care. First, the relevance of mental health and ethical implications are presented. In a second step, care robots and their potential influence on the mental health of individuals in need of care are discussed. The third step shows how fair access to the value of (mental) health can be realized, even and perhaps because care robots are increasingly assigned to care for people. Finally, ethical challenges are discussed, and possible objections are addressed. The focus is ultimately on the importance of care robots, since they can address the issue of mental health, at least to some extent, in a specific technical way.